Game Drone 3D Berbasis Android Menggunakan Game Development Life Cycle (GDLC) - Nugraheny, Dwi; Wibowo, Ilham Satrio; Retnowati, Nurcahyani Dewi; Sunaryo, Heri (MEANS (Media Informasi Analisa dan Sistem), 2023)
Drone racing in Indonesia is starting to gain a lot of interest, but physically making a drone race is not cheap. So with the drone game in the form of an application, the aim is for users to feel the adrenaline interaction of a real drone race but in the form of a game. This Android-based drone race game was made using 3ds Max and Unity software. Application testing includes device testing, alpha testing and interactions which are uploaded to users for response. Testing on 9 devices with different Android versions showed that 7 Android versions with versions 6.0 to 12.0 of the drone race game were successfully run. Testing via alpha testing obtained results that all buttons functioned well. Meanwhile, beta testing is done by uploading the application to the itch.io website. In beta testing there were 130 views, 51 people downloaded it and out of 50 comments, 15 comments said this application was good.